Ferroelectric domain structure of epitaxial (Pb,Sr)TiO3 thin films - Kim, YK; Lee, KS; Baik, S (MATERIALS RESEARCH SOCIETY, 2001)
Epitaxial (Pb1-xSrx)TiO3 (PST, x = 0.0-0.24) thin films were grown on MgO(001) single-crystal substrates by pulsed laser deposition. General x-ray diffraction techniques including theta -2 theta scan and rocking curve were used to determine lattice constants, degree of c-axis orientation, and crystal quality of the tetragonal thin films. The degree of c-axis orientation in the epitaxial PST films increased as Sr concentration (x) increased, which in turn induces the systematic change in the Curie temperature as well as the transformation strain at and below the Curie temperature. An inverse relation between the c-domain abundances and the transformation strains is established.
Keywords: FERROELASTIC FILMS; STRAIN RELAXATION; PHASE-TRANSITION; TITANATE